Multielement Polychromatic 2D Liquid Crystal Dammann Gratings. Issue 3 (6th October 2022) - Zhao, Zimo; Chen, Bohan; Salter, Patrick S.; Booth, Martin J.; O'Brien, Dominic; Elston, Steve J.; Morris, Stephen M.
Abstract: Multielement and multiwavelength switchable Dammann gratings are demonstrated in polymerizable nematic liquid crystal (LC) devices fabricated using two‐photon polymerization direct laser writing. To begin with, a single element 2D Dammann grating, with a diffraction efficiency of around 60%, is fabricated in a thin polymerizable LC layer such that the grating could be activated and deactivated with the application and removal of an external applied voltage. The impact of the fabrication parameters on the resulting intensity distribution in the far‐field diffraction pattern is presented and discussed, along with results for the response times, which are found to be less than that recorded for the regions of the LC device that did not consist of the laser‐written grating. A multielement device is then presented that exhibits two different Dammann gratings that are activated by the application of two different voltage amplitudes. Results for the corresponding far‐field intensity profiles and response times are presented, which demonstrate that high quality laser written switchable Dammann gratings can be fabricated in polymerizable LCs. These switchable elements have potential in programmable beam shaping, microscopy and optical communication devices. Abstract : This paper reports the development of switchable and interchangeable Dammann gratings that have been fabricated into liquid crystal (LC) devices using two‐photon polymerization direct laser writing. When a voltage is applied to the LC device, different 2D Dammann gratings can be activated at different voltage amplitudes, which can be tuned to work at a variety of different wavelengths.